Simulating Evacuation Crowd with Emo-tion and Personality - Juárez, Carlos; Maizanche, Cristian; Matilla, Raul; Mellídez, Sergio (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2018)
Crowd evacuation has attracted great attention, the number of emergencies continues to increase. Thanks to the technology, it is possible to deduce the behavior of the crowd in emergencies, improving security. The multitude enters into a state of panic, so it is necessary to have action protocols for these situations. This work tries to establish a multi-agent model of emotional contagion that simulates the behavior of the crowd in an evacuation. The method is proposed for closed areas such as supermarkets, stadiums, soccer, stadiums, etc. The emotional contagion will accelerate the evacuation, but the congestion will occur if the panic emotion is spread too fast.